Pengaruh Terpaan Media Sosial @Beritasatu terhadap Minat Berdonasi - Hidayatullah, Muhamad Ivan; Safitri, Dini; Putri, K. Y. S.; Sutjipto, Vera Wijayanti; Prananingrum, Elisabeth Nugrahaeni; Sary, Marisa Puspita (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
Aksi Cepat Tanggap or abbreviated as ACT is one of the largest philanthropic institutions in Indonesia. During ACT's development, Bareskrim Polri suspects that there was a misuse of aid funds made by ACT for the victims of the Lion Air JT-610 plane crash in 2018. These findings were conveyed by the police after the Financial Analysis and Transaction Reporting Center or PPATK stated that there was a myriad of financial problems at ACT. This study uses a quantitative approach, with data collection methods using questionnaires. The sampling technique for this study used a census technique so that the population, as well as the sample for this study, were 106 Instagram followers @beritasatu who liked the post entitled